PARTISIPASI KERJA LANSIA PADA RUMAH TANGGA TUNGGAL DI INDONESIA - Diane Putri Prahastiwi; Yogo Aryo Jatmiko (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2023)
The phenomenon of an aging population has occurred in many countries, including Indonesia. The addition of the percentage of elderly people is expected to have a positive impact on the country's economy by becoming an active elderly person. The scope and unit of analysis used in this study are residents aged 60 years and over throughout Indonesia, both working and not working. This study aims to see the effect of living status with the elderly on the work participation of the elderly in Indonesia using the August 2021 Sakernas data. Descriptive statistics and binary logistic regression are used as analytical tools. The results showed that the tendency for the work participation of the elderly in single households was greater than that of the elderly in non-single households. Therefore, policies to improve the welfare of the elderly in single households need to be of concern to the government, both in terms of improving elderly health services, elderly-friendly employment opportunities, or more equitable social security.